2018
DOI: 10.1542/peds.2018-0437
|View full text |Cite
|
Sign up to set email alerts
|

Father-Inclusive Perinatal Parent Education Programs: A Systematic Review

Abstract: There is a need for more evidence-based interventions to support fathers. Clinicians play a key role in engaging fathers in early parent education programs and health care settings. PROSPERO registration number: CRD42017050099.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 79 publications
(104 reference statements)
3
52
0
Order By: Relevance
“…The existing medical model infrequently includes information aimed towards men during prenatal visits. For example, a recent systematic review found only 19 perinatal parent education programs that involved men [34]. The lack of education and content aimed towards men may leave many fathers with unanswered questions and feeling excluded from the process [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The existing medical model infrequently includes information aimed towards men during prenatal visits. For example, a recent systematic review found only 19 perinatal parent education programs that involved men [34]. The lack of education and content aimed towards men may leave many fathers with unanswered questions and feeling excluded from the process [27].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of education and content aimed towards men may leave many fathers with unanswered questions and feeling excluded from the process [27]. This is ultimately a disservice to both parents and the child, as work suggests involving parents in the prenatal period engenders many positive benefits [34]. Moreover, men who become involved during the pregnancy are more likely to continue to be involved later in the child’s life, bringing forth continued benefits [4].…”
Section: Discussionmentioning
confidence: 99%
“…A strength of this study is the involvement of fathers, who are rarely included in studies on interventions to promote parenting [66].…”
Section: Limitations and Strengthsmentioning
confidence: 99%
“…Social support includes family and friends; online peer and professional support (Nieuwboer, Fukkink, & Hermanns, 2013); informal facilitated playgroups (Jackson, 2013; Owen & Anderson, 2015); and professionally led parenting education programs (Murphy, Zweifach, & Hoffman, 2012). A systematic review of father involvement in parenting programs in the perinatal period (J. Y. Lee, Knauer, Lee, MacEachern, & Garfield, 2018) identified a need for early father involvement and a focus on in-home parenting support especially for mothers living with low income.…”
Section: Social Support and Early Developmentmentioning
confidence: 99%